Theory of Mind Profiles in Children With Autism Spectrum Disorder: Adaptive/Social Skills and Pragmatic Competence - Rosello, Belen; Berenguer, Carmen; Baixauli, Inmaculada; García, Rosa; Miranda, Ana (Frontiers in Psychology, 2020)
Theory of Mind (ToM) is one of the most relevant concepts in the field of social cognition, particularly in the case of Autism Spectrum Disorders (ASD). Literature showing that individuals with ASD display deficits in ToM is extensive and robust. However, some related issues deserve more research: the heterogeneous profile of ToM abilities in children with ASD and the association between different levels of ToM development and social, pragmatic, and adaptive behaviors in everyday life. The first objective of this study was to identify profiles of children with ASD without intellectual disability (ID), based on explicit and applied ToM knowledge, and compare these profiles with a group of children with typical development (TD). A second objective was to determine differences in symptom severity, adaptive/social behavior, and pragmatic abilities between the profiles identified. Fifty-two children with a clinical diagnosis of ASD without ID and 37 children with TD performed neuropsychological ToM tasks and two vocabulary and memory tests. In addition, all of their mothers completed different questionnaires about applied ToM abilities, severity of ASD symptoms, adaptive/social skills, and pragmatic competence. Two subgroups were identified in the cluster analysis carried out with explicit and applied ToM indicators. The “Lower ToM abilities” profile obtained significantly lower scores than the “Higher ToM abilities” profile on all the ToM measures. Furthermore, the analysis of covariance, controlling for vocabulary and working memory (ANCOVAs), showed statistically significant differences in applied ToM abilities between the two groups of children with ASD without ID and the group with TD. However, only the group with “Higher ToM abilities” achieved similar performance to the TD group on the verbal task of explicit ToM knowledge. Finally, the “Lower ToM abilities” cluster obtained significantly higher scores on autism symptoms (social and communication domains) and lower scores on adaptive behavior and pragmatic skills than the cluster with “Higher ToM abilities”. Taken together, these findings have implications for understanding the heterogeneity in ToM skills in children with ASD without ID, and their differential impact on social, communicative, and adaptive behaviors.